2015
DOI: 10.1093/ee/nvv062
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofBemisia tabaciGenetic Groups in India

Abstract: The whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is a phloem-feeding, economically important pest of crops worldwide. In addition to direct damage, it also vectors a number of plant viruses belonging to the family Geminiviridae. Its populations differ biologically with respect to insecticide resistance, virus transmission and host range. Therefore, understanding genetic variation among populations is important for management. We sequenced 850 bp of the mitochondrial COI (mtCOI) gene from B. tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 28 publications
8
38
0
1
Order By: Relevance
“…As B. tabaci species differ significantly in their sensitivity to insecticides with the invasive species MEAM1 and MED having a high propensity for developing resistance against many pesticides (Horowitz et al 2007;Horowitz and Ishaaya 2014), a comprehensive knowledge of whitefly species abundance is essential for a rational use of insecticides to avoid ineffective protection measures that burden farmer's health and environment. In recent more extensive investigations of B. tabaci species distribution in India Ellango et al (2015) and Prasanna et al (2015) found the indigenous Asia II 1 genotype in high abundance confirming the finding of Asia II 1 in three consecutive years in the North in this study. In another study, Asia1 was found to be predominant in the North of India, butin the South a higher diversity of B. tabaci species was found (ChowdaReddy et al 2012;Ellango et al 2015), whereas in this study Asia II 8 was predominant in the south.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As B. tabaci species differ significantly in their sensitivity to insecticides with the invasive species MEAM1 and MED having a high propensity for developing resistance against many pesticides (Horowitz et al 2007;Horowitz and Ishaaya 2014), a comprehensive knowledge of whitefly species abundance is essential for a rational use of insecticides to avoid ineffective protection measures that burden farmer's health and environment. In recent more extensive investigations of B. tabaci species distribution in India Ellango et al (2015) and Prasanna et al (2015) found the indigenous Asia II 1 genotype in high abundance confirming the finding of Asia II 1 in three consecutive years in the North in this study. In another study, Asia1 was found to be predominant in the North of India, butin the South a higher diversity of B. tabaci species was found (ChowdaReddy et al 2012;Ellango et al 2015), whereas in this study Asia II 8 was predominant in the south.…”
Section: Discussionsupporting
confidence: 89%
“…In recent more extensive investigations of B. tabaci species distribution in India Ellango et al (2015) and Prasanna et al (2015) found the indigenous Asia II 1 genotype in high abundance confirming the finding of Asia II 1 in three consecutive years in the North in this study. In another study, Asia1 was found to be predominant in the North of India, butin the South a higher diversity of B. tabaci species was found (ChowdaReddy et al 2012;Ellango et al 2015), whereas in this study Asia II 8 was predominant in the south. A first report of B. tabaci MEAM1 in India was from Banks et al (2001) who collected this invasive species from infected tomato in the Kolar district.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Extensive information is available on the insecticide resistance status of Mediterranean (MED) and the Middle East-Asia Minor 1 (MEAM 1) genetic groups, known in older literature as the Q and B biotypes, respectively1. Although Indian geographical regions display an enormous diversity of B. tabaci with the presence of nine out of the 36 genetic groups recorded so far5253, only limited literature is available on the insecticide resistance status of Indian contingent of B. tabaci species complex101227. The present investigation attempts to take a snapshot view of resistance development in field populations of B. tabaci (collected across agro-climatic zones) against OPs, synthetic pyrethroids and neonicotinoids concurrently used for controlling B. tabaci in India along with information on their genetic group status.…”
mentioning
confidence: 99%